1986
DOI: 10.1159/000249367
|View full text |Cite
|
Sign up to set email alerts
|

Oral Gold Therapy (Auranofin) in Pemphigus vulgaris

Abstract: Auranofin (AF), an oral gold salt, was given for 9–18 months to 3 patients with pemphigus vulgaris. There was a slight improvement with significant oral pain relief in 2, and a complete remission in 1. Two patients including the one with the remission, subsequently flared up under AF therapy. Although AF is said to be better tolerated than parenteral gold this limited series suggests that it does not seem to have a superior therapeutic effect in PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Oral gold is not more effective than parenteral gold, according to one report of 3 patients. 46 In 1984 Poulin et al reported a series of 13 patients with PV who received combination therapy consisting of prednisone (varying doses) and gold (50 mg/wk). 47 Seven of the patients had complete remission that required no further treatment.…”
Section: Management Of Pemphigus Vulgarismentioning
confidence: 99%
“…Oral gold is not more effective than parenteral gold, according to one report of 3 patients. 46 In 1984 Poulin et al reported a series of 13 patients with PV who received combination therapy consisting of prednisone (varying doses) and gold (50 mg/wk). 47 Seven of the patients had complete remission that required no further treatment.…”
Section: Management Of Pemphigus Vulgarismentioning
confidence: 99%
“…Gold decreases autoantibody titers in patients with pemphigus without directly suppressing antibody synthesis or impairing binding of autoantibodies to epidermal antigens. Oral gold does not seem to be more effective than parenteral preparations Salomon and Saurat (1986). The oral form, auranofin, is easier to use and less toxic.…”
Section: Aurothioglucosementioning
confidence: 93%
“…40 Although gold sodium thiomalate given intramuscularly may be beneficial in patients with pemphigus, oral therapy (with auranofin) is usually not. 41 Although gold was once commonly used as a second-line agent in pemphigus, it is now given rarely, a development that reflects its efficacy in only a subgroup of patients and the potential risk of side effects during its prolonged administration.…”
Section: Chrysotherapymentioning
confidence: 99%